2016
DOI: 10.1186/s40478-016-0384-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Keap1/Nrf2 stress response pathway in autophagic vacuolar myopathies

Abstract: Nrf2 (nuclear factor [erythroid-derived 2]-like 2; the transcriptional master regulator of the antioxidant stress response) is regulated through interaction with its cytoplasmic inhibitor Keap1 (Kelch-like ECH-associated protein 1), which under basal conditions targets Nrf2 for proteasomal degradation. Sequestosome 1 (SQSTM1)/p62–a multifunctional adapter protein that accumulates following autophagy inhibition and can serve as a diagnostic marker for human autophagic vacuolar myopathies (AVMs)–was recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This accumulation may enhance the isolation of Keap1 by p62. In addition, there is reported that CQ can activate Nrf2/HO-1 pathway ( 14 ). Therefore, we speculated that the accumulation of p62 and degradation of Keap1 induced by DC32 were controlled by PI3K-III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This accumulation may enhance the isolation of Keap1 by p62. In addition, there is reported that CQ can activate Nrf2/HO-1 pathway ( 14 ). Therefore, we speculated that the accumulation of p62 and degradation of Keap1 induced by DC32 were controlled by PI3K-III.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to competing with Nrf2 for the Keap1 binding site and sequestering Keap1 into aggregates, p62 also brings Keap1 to autolysosomes for degradation in selective autophagy. The Nrf2-Keap1 interaction, which is blocked by the accumulation of p62 and Nrf2, is increased in the cytoplasm, resulting in activation of the Nrf2/HO-1 pathway ( 12 , 14 16 ). In addition, p62/SQSTM1 is also a target gene of Nrf2, and its expression can be induced by Nrf2 under oxidative stress conditions, further facilitating the activation of Nrf2 by blocking its degradation ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, several studies have indicated that accumulation of p62 in addition to ubiquitylated protein aggregates results in various disorders, which are caused by disruption of Nrf2 degradation and its persistent activation under autophagy-deficient conditions (Duleh et al, 2016). Notably, to date, the biological functions of p62 under diverse pathophysiological processes remain elusive and modulating functions of accumulated p62 in liver disease have seldom been reported in autophagy sufficiency conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Further signs of antioxidant responses include overexpression of HMOX1, which is considered one of the most sensitive and reliable indicators of cellular oxidative stress (Maamoun et al 2016 ), TXNRD1, a pivotal intracellular redox sensor and antioxidant enzyme (Schmidt 2015 ), NQO1, which is essential for cell defense against ROS (Di Francesco et al 2016 ), and FTH1, a major iron storage protein that can protect cells from the toxic effects of iron as well as other free radical producing stresses (Funauchi et al 2015 ). In addition, downregulation of the pro-apoptotic BNIP3L, which plays an important role in hypoxia-dependent cell death (Bellot et al 2009 ) and upregulation of SQSTM1, a multifunctional adapter protein that accumulates following autophagy inhibition (Duleh et al 2016 ), was also observed. This could explain the relatively moderate impact of the tested DEPs on cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%